Church-State relations : an exegetical study on Romans 13:1-7 and it relevance to the Philippine context - Kole, Armando Sarahina ([Quezon City] : SEAGST, St. Andrew's Theological Seminary, 1994)
This thesis deals with the topic, "Church-State relations: an Exegtical study on Romans 13:1-7 and its relevance to the Philippine context". It is a subject which many Christians consider as "controversial" in the light of the modern concept of the state especially among the liberal democratic countries of the world. Many have asked the questions, "Is Paul's instruction to submit to the governing authorities in Romans 13: 1 still applicable today?" " And to what extent should a Christian obey the civil authorities?"
The aim of the first major section of the thesis is to find out the meaning of the text in Romans 13:1-7 from the original Greek language by applying the exegetical principles.
In partial fulfillment of the requirement for the Degree Master of Theology
A thesis presented to the faculty of the South East Asia Graduate School of Theology, St. Andrew's Theological Seminary.
Thesis (M. Theo.)- St. Andrew's Theological Seminary